Effect of water nanoconfinement on the dynamic properties of paramagnetic colloidal complexes. Issue 31 (2nd August 2021) - Bergamasco, Luca; Morciano, Matteo; Fasano, Matteo
Abstract : We analyze the tumbling motion of a solvated paramagnetic complex close to confining particles. Molecular dynamics data is interpreted via mechanistic modeling, towards design of improved nanovectors for local enhancement of relaxation properties. Abstract : The anomalous behavior of confined water at the nanoscale has remarkable implications in a number of nanotechnological applications. In this work, we analyze the effect of water self-diffusion on the dynamic properties of a solvated gadolinium-based paramagnetic complex, typically used for contrast enhancement in magnetic resonance imaging. In particular, we examine the effect of silica-based nanostructures on water behavior in the proximity of the paramagnetic complex via atomistic simulations, and interpret the resulting tumbling dynamics in the light of the local solvent modification based on the Lipari–Szabo formalism and of the fractional Stokes–Einstein relation. It is found that the local water confinement induces an increased "stiffness" on the outer sphere of the paramagnetic complex, which eventually reduces its tumbling properties. These model predictions are found to explain well the relaxivity enhancement observed experimentally by confining paramagnetic complexes into porous nanoconstructs, and thus offer mechanistic guidelines to design improved contrast agents for imaging applications.